Perceived sounds and their reported level of disturbance in intensive care units: A multinational survey among healthcare professionals. - Nicole Ruettgers; Aileen C Naef; Marilyne Rossier; Samuel E J Knobel; Marie-Madlen Jeitziner; Martin Grosse Holtforth; Bjoern Zante; Joerg C Schefold; Tobias Nef; Stephan M Gerber (PLoS ONE, 2022)
Purpose The noise levels in intensive care units have been repeatedly reported to exceed the recommended guidelines and yield negative health outcomes among healthcare professionals. However, it is unclear which sound sources within this environment are perceived as disturbing. Therefore, this study aimed to evaluate how healthcare professionals in Germany, Switzerland, and Austria perceive the sound levels and the associated sound sources within their work environment and explore sound reduction strategies. Material and methods An online survey was conducted among 350 healthcare professionals working in intensive care units. The survey consisted of items on demographic and hospital data and questions about the perception of the sound levels [1 (strongly disagree) to 5 (strongly agree)], disturbance from sound sources [1 (not disturbing at all) to 5 (very disturbing)], and implementation potential, feasibility, and motivation to reduce sound reduction measures [1 (not high at all) to 5 (very high)]. Results Approximately 69.3% of the healthcare professionals perceived the sound levels in the ICUs as too high. Short-lasting human sounds (e.g. moans or laughs) [mean (M) ± standard deviation (SD) = 3.30 ± 0.81], devices and alarms (M ± SD = 2.67 ± 0.59), and short-lasting object sounds (M ± SD = 2.55 ± 0.68) were perceived as the most disturbing sounds. Reducing medical equipment alarms was considered to have greater implementation potential [M ± SD = 3.62 ± 0.92, t(334) = -7.30, p < 0.001], feasibility [M ± SD = 3.19 ± 0.93, t(334) = -11.02, p < 0.001], and motivation [M ± SD = 3.85 ± 0.89, t(334) = -10.10, p < 0.001] for reducing the sound levels. Conclusion This study showed that healthcare professionals perceive short-lasting human sounds as most disturbing and rated reducing medical equipment alarms as the best approach to reduce the sound levels in terms of potential, feasibility, and motivation for implementation.